Violence and Community: Collective and Cultural Trauma in Black America - Yu, Michael (Lumen et Vita, 2016)
The relationship between law enforcement and predominantly black communities has been characterized by mistrust, violence, and victimization. Recently, this issue has entered into the national conversation, sparked by the deaths of Michael Brown, Eric Garner, Sandra Bland, Samuel Dubose, Tamir Rice, Laquan McDonald, and countless other black individuals. The present paper presents the experience of black communities in the United States as an experience of collective and communal trauma. First, collective trauma is conceptualized and distinguished from individual trauma writ large from a sociological perspective with Ignacio Martin Baró and Jeffrey Alexander. Communal trauma is a phenomenon that is different than individual trauma because of its social and communal implications. Next, the experience of black communities in light of consistent patterns of police violence is named as collective trauma. Michelle Alexander’s The New Jim Crow will be used, as well as Atlantic correspondent Ta-Nehisi Coates. The final section proposes a pastoral response to the communal trauma of Black communities, divided into two parts. The first is a look inwards towards organized Christianity’s complicity in the terrorism of Black communities and the benefits that are gained from their subjugation, and the second looks outwards, proposing a stance of solidarity, courage, and righteous indignation that actively works towards the liberation of marginalized communities.